(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Employee Retention is a process in which the employees are encouraged to remain with the organization for the maximum period of time or until the completion of the project. With the increasing attrition in organizations especially in Indian Public Sector Organization, it has become a question of study. This paper deals with factors that are affecting the retention of employees in Indian Public Sector Organization and its impact on the Organization. The present paper uses Frequency and Cross-tab methodology for identifying the major factors relating to employee retention. The survey has been conducted in National Thermal Power Corporation Ltd (NTPC) Ramagundam.